EFFECTIVENESS OF INTERGENERATIONAL PROGRAM IN IMPROVING COMMUNITY SENIOR CITIZENS’ GENERAL HEALTH AND HAPPINESS - Hsu S. C.; Rong J. R.; Lin H. R.; Liu C. Y (European Scientific Journal, ESJ, 2014)
Intergenerational programs (IGPs) encourage senior citizens tocontinue engaging in social participation, preserving their independence, andenriching their later life. However, IGPs in Taiwan (IGPs-T) are notprevalent and generally more apply between children and senior citizensexist only, which lack in-depth exchanges the senior citizen‘s life experienceand communication the young people. Relevant empirical results regardingthe effectiveness of IGPs activities on community senior citizens‘ health andhappiness are lacking. The objective of this study was to improve the mutualunderstanding and inclusion between community senior citizens and younggenerations, thereby improving the senior citizens‘ physical and mentalhealth functions and happiness.This was a two-group pre and post-test quasi-experimental studydesign and purposive sampling was used to recruit community senior citizensin Taipei City as research participants (N = 118). The experimental group (n= 55) received 90-min IGP-T activities once a week for 8 weeks. The controlgroup (n = 63) received general health services providing by communityhealth nurses in community.The outcomes of the experimental group significant progress in thehappiness (t=2.82, p=.007), and emotional well-being (EWB) (t=4.61,p≦.001) from pre-test to post-test. And the experimental group wassignificantly superior to control group in perceived health status (PHS)(t=3.79, p≦.001), happiness (t=3.82, p≦.001), and emotional well-being(EWB) (t=4.93, p≦.001) at post-test, and achieve a statistically significantdifference.